Low-dose emapalumab treatment in refractory macrophage activation syndrome secondary to adult onset still’s disease/systemic lupus erythematosus: insights from nine cases - Chen, Jie; Zhao, Liling; Lin, Yanwei; Lian, Xinyue; Wang, Haiting; Gu, Liyang; Wang, Ran; Wang, Xiaodong; Ye, Shuang; Fu, Qiong (Frontiers in Immunology, 2025)
ObjectiveMacrophage activation syndrome (MAS) is frequently secondary to rheumatic diseases, with features including a cytokine storm and hemophagocytosis. Emapalumab is a monoclonal antibody that targets interferon-γ and has the ability to precisely regulate cytokines. This study aimed to investigate the efficacy and safety of low-dose emapalumab for patients with refractory MAS in the Chinese population.MethodsFrom January 2022 to July 2024, 9 patients with MAS secondary to adult-onset Still’s disease (AOSD) or systemic lupus erythematosus (SLE) received low-dose emapalumab following no response to prior conventional therapies. The laboratory parameters, therapeutic response, and safety were assessed following low-dose emapalumab-based treatment.ResultsOf the nine MAS patients, 5 patients were secondary to AOSD and 4 patients were secondary to SLE. The overall response rate was 66.7% (6/9), 77.8% (7/9), 88.9% (8/9) and 88.9% (8/9) at week 1, 2, 4 and week 8, respectively. At the end of the follow-up period, up to 88.9% (8/9) of patients achieved complete remission. All patients demonstrated improvement or normalization of clinical manifestations and laboratory parameters. Notably, the median prednisone-equivalent dose for the patients was reduced by 85.5% during the treatment. Cytomegalovirus infection occurred in 33.9% (3/9) of patients, with no occurrence of serious adverse events reported.ConclusionOur findings suggest that low-dose emapalumab may be a promising salvage option for refractory MAS in the Chinese population, but confirmation in larger prospective studies is required.